PAULO FREIRE E A EDUCAÇÃO DA INFÂNCIA DAS CLASSES POPULARES EM REFLEXÕES, IMAGENS E MEMÓRIAS REVELADAS - Peloso, Franciele Clara (2009)
This work shows an approach between Paulo Freire’s thought and the lower classes Childhood Education. The aim of the research was to investigate how the Paulo Freire’s theory can be resignified in different contexts toward Childhood Education. To accomplish this task works of Paulo Freire and messages sent by scholars of his work were analyzed. These sources pointed to memories about the relation of the Paulo Freire’s work and the concern about childhood and children. The justification of this work is set to a comprehension, from Freirian assumptions, to the condition of oppression on which many children from the lower classes are submitted by the fact of being devoid of fundamental guarantees such the right of Education, housing, health care, good quality leisure, among other aspects. The difficulties of access to such guarantees contribute for the dehumanization process of these children, taking into account these are limits to their ontological vocation of “be more”: the humanization. This is a qualitative research of empiric-theoretical bias. The theoretical framework was build on the Paulo Freire’s work, and from authors of History, Philosophy, Anthropology, Childhood Sociology, Pedagogy, Children’s Education and critics of Childhood Education. The sources used in this research are of bibliographic, empirical and documental nature. The methodological procedures used were: the analysis of Paulo Freire’s work from 1991 to 2000 period; literature review of academicals works that approach the Freirian assumptions on the Childhood Education and testimonies analysis obtained by established contacts with Freire’s work scholars. The main considerations of this study were: Freire mentioned on many of his works about distinct Childhoods and Children. In relation of the academicals works many are near of the Freirian assumptions concerning to the understanding of the child as a subject that is and is being and also with about pedagogical space on which the children may develop their autonomy. Concerning the impression of the Freire’s work most of the scholars mentioned the reductionism presented on the readings of Paulo Freire’s work; some readers do not associated Freirian assumptions with questions related to Childhood Education. Under this perspective it was possible to make it evident that the Freirian thought is one of the most significant for changing on the Education scope, especially on the rescue of the Childhood Education for lower classes children.